2012
DOI: 10.1007/s00401-012-0963-y
|View full text |Cite
|
Sign up to set email alerts
|

Nigrostriatal overabundance of α-synuclein leads to decreased vesicle density and deficits in dopamine release that correlate with reduced motor activity

Abstract: α-Synuclein (α-syn) is a presynaptic protein present at most nerve terminals, but its function remains largely unknown. The familial forms of Parkinson's disease associated with multiplications of the α-syn gene locus indicate that overabundance of this protein might have a detrimental effect on dopaminergic transmission. To investigate this hypothesis, we use adeno-associated viral (AAV) vectors to overexpress human α-syn in the rat substantia nigra. Moderate overexpression of either wild-type (WT) or A30P α-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
105
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 59 publications
8
105
0
Order By: Relevance
“…Synapses of mice knocked out for ␣S showed diminished levels of synaptic vesicles in the reserve pool (2), whereas overexpression of ␣S is reported to inhibit re-clustering of synaptic vesicles, thereby reducing neurotransmitter release (15). These and other reports (21)(22)(23) suggest that ␣S interacts directly with membranes to control cycles of synaptic vesicle release.…”
Section: ␣-Synuclein (␣S)supporting
confidence: 76%
“…Synapses of mice knocked out for ␣S showed diminished levels of synaptic vesicles in the reserve pool (2), whereas overexpression of ␣S is reported to inhibit re-clustering of synaptic vesicles, thereby reducing neurotransmitter release (15). These and other reports (21)(22)(23) suggest that ␣S interacts directly with membranes to control cycles of synaptic vesicle release.…”
Section: ␣-Synuclein (␣S)supporting
confidence: 76%
“…Previous studies from our group and others have established that the decrease in TH + neuron number, induced by α-syn overexpression in this rat model, is due to neuronal loss rather than the loss of dopaminergic phenotype. In these studies, quantification of Nissl-positive or cresyl violet-positive cells in the SNc revealed a reduction of the number of positive cells, after α-syn overexpression, compared with the noninjected side, confirming that the neurons had indeed degenerated (25,27).…”
Section: Plk2 Wt But Not the Kinase-dead Mutant Suppresses α-Syn-inmentioning
confidence: 67%
“…The decrease of dopamine overflow in these mice is not dependent on dopamine D2 autoreceptors misfunctioning or changes in dopamine re-uptake , thus indicating that other molecules, affected by the absence of α-syn, contribute to this phenomenon. Similar to the absence of α-syn, the increase of its protein levels in the nigrostriatal system causes a decrease of vesicle density and reduces dopamine release, thus promoting motor deficits (Garcia-Reitbock et al, 2010;Gaugler et al, 2012;Lundblad et al, 2012;Tofaris et al, 2006).…”
Section: Introductionmentioning
confidence: 99%